Impact of active and passive hypoxia as re-warm-up activities on rugby players` performance - Ramos-Campo, D. J.; Malta, J.; Olcina, G.; Timón, R.; Raimundo, A.; Tomas-Carus, P. (International Journal of Environmental Research and Public Health, 2020)
IThe aim of this study was to analyse the effect of four types of re-warm-up (R-WU) activity, namely rest in normoxia (RN) at FiO2 = 20.9%, rest in hypoxia (RH) at FiO2 = 15%, activity (4 × 5 jumps/15 s) in normoxia (AN) and activity in hypoxia (AH) on physical performance. Ten elite male rugby players completed a 15-min warm-up followed by one of the 15-min randomized R-WU strategies. After R-WU, countermovement jump (CMJ), 20 m sprint and repeat sprint ability (RSA) tests were assessed. Compared to passive strategies (RN and RH), tympanic temperature was higher after active R-WU (AN and AH) (p = 0.016). Higher values of CMJ height (p = 0.037) and 20 m sprint (p = 0.02) were found in AH than in RN. In addition, mean RSA was lower (p = 0.008) in AH than in RN and RH. Blood lactate concentration was higher (p = 0.007) after RN and AN strategies than after AH. Muscle O2 saturation (p = 0.021) and total Hb (p = 0.042) were higher after AH than after the other three conditions and after RN, respectively. Therefore, an active R-WU under hypoxia could be useful to elite rugby players, once it had attenuated the decline in tympanic temperature during a 15-min period after warm-up, improving jump, sprint and RSA performance.